PROFITABILITY, GROWTH OPPORTUNITIES, LEVERAGE, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN - Lestari, Diyan (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
Dividend policy is one of the most important activities which investors will wait and interpret the action as a positive signal because it indicates the firm performance (a firm which distributes dividend considered has better performance). Dividend policy is a strategical decision since it will impact firm credibility and firm value. This study aims to analyze the effect of profitability, growth opportunities, leverage, and size on dividend policy in the automotive industry which listed in Indonesia Stock Exchange from 2009 to 2016. The automotive industry is one of Indonesian middle-class standard measurement and it will be the biggest automotive ASEAN market in 2019. We use secondary data and use pooling regression (panel regression) to analyze the result of the study. The result shows that profit margin, return on asset, and size has positive and statistically significant on dividend policy, growth opportunities has the negative effect and statistically significant on dividend policy, while return on equity and leverage do not affect the dividend policy. Keywords: Profitability, growth opportunities, leverage, firm size, dividend policy